2022
DOI: 10.1093/jpepsy/jsac007
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Adjustment and Parent–Infant Relations in Mothers of Premature Infants: Thematic Analysis Using a Multisensory Approach

Abstract: Objective The aim of the study was to explore mothers’ experiences of having an infant born prematurely (28–32 weeks gestation). In particular, the study aimed to explore the developing parent–infant relationship 12–30 months since birth and the developing parental identity during hospitalization and discharge. Methods Twelve mothers, aged between 22 and 43, participated in the semi-structured interviews. The mean age of infa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…In addition, when women also had a baby with neonatal complications, then their ability to perform caretaking procedures or appraise the situation was found to be negatively impacted. Indeed, some studies have shown that mothers of infants with complications often face a significant care burden when they encounter excessive and complex parenting tasks (Barroso et al, 2016; Eom & Im, 2019; Pan & Gong, 2022; Sandoz et al, 2022; Suarez et al, 2022). These observations provide some new and valuable insights into the distinct aspect of parenting self‐efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, when women also had a baby with neonatal complications, then their ability to perform caretaking procedures or appraise the situation was found to be negatively impacted. Indeed, some studies have shown that mothers of infants with complications often face a significant care burden when they encounter excessive and complex parenting tasks (Barroso et al, 2016; Eom & Im, 2019; Pan & Gong, 2022; Sandoz et al, 2022; Suarez et al, 2022). These observations provide some new and valuable insights into the distinct aspect of parenting self‐efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Not being responsible for the care of their infant on a neonatal ward can make parents 'not feel like parents'. 2 Besides the parental role alteration, factors such as physical separation, the infant's changing clinical condition and the technical environment of the ward impose an important source of parental stress. 3,4 As this stress impacts both parental and infant (short-and long-term) health, 5 optimising closeness during an infant's admission to a neonatal ward should be a priority.…”
Section: Introductionmentioning
confidence: 99%
“…However, developing this closeness is challenging during infant hospitalisation after birth. Not being responsible for the care of their infant on a neonatal ward can make parents ‘not feel like parents’ 2 . Besides the parental role alteration, factors such as physical separation, the infant's changing clinical condition and the technical environment of the ward impose an important source of parental stress 3,4 .…”
Section: Introductionmentioning
confidence: 99%